2006
DOI: 10.1080/00288233.2006.9513717
|View full text |Cite
|
Sign up to set email alerts
|

Populations of soil organisms under continuous set stocked and high intensity‐short duration rotational grazing practices in the central tablelands of New South Wales (Australia)

Abstract: Grazing management practices modify soil structure, which, in turn, alters the behaviour and population dynamics of soil-inhabiting organisms. Monitoring of changes in abundance and richness of soil organisms is vital in determining the sustainability of grazing regimes. In this paper, populations of soil organisms were compared-using abundance and population trends as an indicator of diversity-in two different grazing practices (a) conventional, set stocked (SS) grazing regime and (b) high intensity-short dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…Contrary to H1, excluding the largest herbivores, the ungulates, did not alter abundance, richness or community structure of any of the microarthropod groups in our study. This contrasts several studies conducted in meadow systems where effects of domestic ungulates on soil microarthropods were evident and mostly caused by disturbance [ 14 , 17 , 39 ]. Lessard et al [ 40 ] demonstrated a negative effect of white-tailed deer on soil microarthropod richness in the Great Smoky Mountains National Park, Tennessee (USA), and attributed this to a decrease in litter quantity.…”
Section: Discussioncontrasting
confidence: 75%
“…Contrary to H1, excluding the largest herbivores, the ungulates, did not alter abundance, richness or community structure of any of the microarthropod groups in our study. This contrasts several studies conducted in meadow systems where effects of domestic ungulates on soil microarthropods were evident and mostly caused by disturbance [ 14 , 17 , 39 ]. Lessard et al [ 40 ] demonstrated a negative effect of white-tailed deer on soil microarthropod richness in the Great Smoky Mountains National Park, Tennessee (USA), and attributed this to a decrease in litter quantity.…”
Section: Discussioncontrasting
confidence: 75%
“…It typically increases ground cover, litter cover, and the cover of economically desirable pasture species (40,41), and it facilitates improved water infiltration (42). It also can have benefits for microarthropods (43) and for soil chemistry, leading to reduced nitrate and phosphorus levels (41). Despite these benefits, fast-rotational grazing has limitations (44), and like all grazing systems, it depends on appropriate management decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Bulk density is also inversely related to the SOM (da Silva et al 1997;Gifford and Roderick 2003) and their interaction can become an important factor in the effectiveness of grazing systems. Time-controlled grazing has been shown to improve soil physical condition through converting the above-ground organic matter to litter without causing soil compaction (Goodloe 1969) and to increase the abundance of micro-arthropods in the -10 cm soil depth (Tom et al 2006). However, Dormaar et al (1989) reported that TC grazing had a negative effect on bulk density, due to compaction by grazing animals.…”
Section: Introductionmentioning
confidence: 99%